2017
DOI: 10.1007/s00726-017-2491-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural complexity and functional diversity of plant NADPH oxidases

Abstract: Plant NADPH oxidases also known as respiratory burst oxidase homologs (Rbohs) are a family of membrane-bound enzymes that play diverse roles in the defense response and morphogenetic processes via regulated generation of reactive oxygen species. Rbohs are associated with a variety of functions, although the reason for this is not clear. To evaluate using bioinformatics, the possible mechanisms for the observed functional diversity within the plant kingdom, 127 Rboh protein sequences representing 26 plant speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 97 publications
1
16
0
Order By: Relevance
“…This generates a positive feedback loop between generation of ROS and Ca 2+ signals. Conversely, S-nitrosylation of the cysteine residue in the C-terminus was shown to inhibit AtRBOHD activity; as this residue is conserved in the other 18 AtRBOH members, such a regulatory mechanism may be hypothesized to be universal for the family ( Kaur et al , 2018 ). In Arabidopsis, NO generation is rapidly stimulated by H 2 O 2 , so it is tempting to think that this mechanism may serve as a feedback loop, terminating the RBOH-generated ROS signal.…”
Section: Plant Nox Function and Regulation: The Role Of Intracellularmentioning
confidence: 99%
“…This generates a positive feedback loop between generation of ROS and Ca 2+ signals. Conversely, S-nitrosylation of the cysteine residue in the C-terminus was shown to inhibit AtRBOHD activity; as this residue is conserved in the other 18 AtRBOH members, such a regulatory mechanism may be hypothesized to be universal for the family ( Kaur et al , 2018 ). In Arabidopsis, NO generation is rapidly stimulated by H 2 O 2 , so it is tempting to think that this mechanism may serve as a feedback loop, terminating the RBOH-generated ROS signal.…”
Section: Plant Nox Function and Regulation: The Role Of Intracellularmentioning
confidence: 99%
“…Ten and nine Rbohs have been identified from Arabidopsis and rice, referred to as AtRbohA–AtRbohJ and OsRbohA–OsRbohI, respectively ( Torres et al, 1998 ). Previous studies suggest they have distinct spatio-temporal expression, enzyme activity, and functional diversification ( Lin et al, 2009 ; Kaur and Pati, 2018 ; Kaur et al, 2018 ; Kaya et al, 2019 ). AtrbohB fulfills important roles in the germination of Arabidopsis seeds through variant splicing transcripts ( Muller et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Plant respiratory burst oxidase homologs, also known as NADPH oxidases, are the most crucial enzymes in ROS-producing system (Ben Rejeb et al, 2015;Marino, Dunand, Puppo, & Pauly, 2012;Suzuki et al, 2011). The rice genome contains nine Rbohs (Kaur et al, 2018), we found that except the three genes of OsRboh6, OsRboh8, and OsRboh9, the other six OsRbohs showed significantly enhanced expression in the anthers of ltt1 ( Figure 4a), which should be largely responsible for the over accumulated ROS in the mutant.…”
Section: Ltt1 Shows Differential Expression Of Ros Homeostasis Genementioning
confidence: 85%